2021
DOI: 10.1590/s1980-657420210000159
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, TV viewing, and human development index in Brazilian adolescents: Results from the National School Health Survey

Abstract: This study aimed to examine the association between physical activity (PA) indicators and TV viewing as a function of the Human Development Index (HDI). Method: This cross-sectional study was based on data from the National School Health Survey, which was composed of 102,072 students (14.28±1.03; 51.3% girls). Total PA, active commuting to school (ACS) and TV viewing were assessed by questionnaires and classified through a gradual scale ranging from "F" (low) to "A+" (high). The correlation between total PA, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
4
0
3
Order By: Relevance
“…In this sense, it is suggested that the Northern and Northeastern regions of the country, with lower HDI, are susceptible to lower levels of physical activity. According to results, higher prevalence of physical activity was found among adolescents in the Midwestern, Southern and Southeastern regions of Brazil 6 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this sense, it is suggested that the Northern and Northeastern regions of the country, with lower HDI, are susceptible to lower levels of physical activity. According to results, higher prevalence of physical activity was found among adolescents in the Midwestern, Southern and Southeastern regions of Brazil 6 .…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, understanding the importance of the school structure as an indicator that provides opportunities for the practice of physical, sporting and leisure activities, allows organization and government actions to encourage PA and combat sedentary lifestyles among young people 4,5 . In Brazilian states, greater adherence to physical activity is associated with higher human development indexes (HDI) 6 , which may reflect, among other elements, the population's access to education and health 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(50,51) Nos estados brasileiros, observa-se que a maior adesão à atividade física está correlacionada a índices mais elevados de Desenvolvimento Humano, o que pode refletir, entre outros fatores, como o acesso da população à educação e à saúde. (14,52,53) A literatura indica que a quantidade de oportunidades de atividade física oferecidas pelas escolas está associada à situação econômica e de desenvolvimento em que estão inseridas. (14,52) no entanto, elementos culturais também desempenham um papel significativo.…”
Section: Atividade Física Em Adolescentesunclassified
“…(14,52,53) A literatura indica que a quantidade de oportunidades de atividade física oferecidas pelas escolas está associada à situação econômica e de desenvolvimento em que estão inseridas. (14,52) no entanto, elementos culturais também desempenham um papel significativo. A valorização do desporto e das atividades físicas, que varia culturalmente, pode servir como potenciais barreiras ou facilitadores para esse indicador.…”
Section: Atividade Física Em Adolescentesunclassified